Stable Li‐Metal Deposition via a 3D Nanodiamond Matrix with Ultrahigh Young's Modulus. Issue 11 (29th May 2019) - Zhang, Weidong; Fan, Lei; Tong, Zheming; Miao, Jiazhi; Shen, Zeyu; Li, Siyuan; Chen, Fang; Qiu, Yongcai; Lu, Yingying
Abstract: The practical usage of high‐energy lithium metal batteries remains a great challenge mainly due to the formation of uneven lithium deposition and huge volume fluctuation on the anode side, which increases the potential risks of a cell short‐circuit. Herein, a nanodiamond‐Li composite anode (ND‐Li) is created using a facile thermal infusion strategy, which can mechanically confine active Li‐metal in the ND matrix and minimize the electrode volume change during electrochemical cycling with high areal capacities. The geometrically restrictive ND matrix with ultrahigh modulus can deform the uneven lithium deposition mechanically and confine the deposition to the ND matrix. Owing to the 3D rigid skeleton, low stripping/plating overpotential (≈60 mV) can be achieved for a ND‐Li anode under a high current density of 10 mA cm −2, whereas the overpotential of a bare Li foil anode is almost seven times larger than the ND‐Li matrix. When a ND‐Li anode pairs with a S cathode, a high capacity of 607.3 mAh g −1 at 1 C and stable long‐term cyclability over 500 cycles can be achieved. Abstract : A nanodiamond‐Li composite anode (ND‐Li) is created using a facile thermal infusion strategy. Lithium metal can be embedded densely in the interconnected nanosized pores within the ND matrix during cycling, which is a joint result of an ultrahigh Young's modulus and a small Poisson ratio of ND.